1512 A Service Evaluation of Transoral Laser Resection Procedures for Oral Cancer and Dysplasia. (12th October 2021) - Amin, A; Twigg, J; Bowe, C; Ho, M
Abstract: Aim: The use of the diode laser is a frequently employed treatment modality in primary surgical excision, especially for early oral cancer. This is due to advantages offered in precision of excision, and potential reduced post-operative pain compared to other excision methods. Additionally, haemostasis can often be obtained simultaneous to excision. Despite frequent use of laser excision for oral cancer/dysplasia, there is limited information on the incidence of postoperative complications. Method: Data was collected retrospectively by review of electronic healthcare records for a 5-year period (Jan 2015-Jan 2020) for patients who underwent transoral laser excision of oral dysplasia in a major UK teaching hospital. The number of short (<30 days) and longer-term complications was evaluated and categorised using the Clavien-Dindo classification. Results: A total 260 patients received diode laser resection for oral cancer/dysplasia in this period. Approximately one third of patients had the diagnosis of SCC and 52% of patients were treated on a day case basis. Approximately one third of patients experienced postoperative complications.; including positive or close resection margins (16%), bleeding (8%), superficial infection (6%) and significant postoperative pain (2%). A total of 16% of patients required further treatment in theatre (Clavien-Dindo IIIb). Conclusions: The use of lasers for excision of oral tumours and dysplastic lesions is a frequently employed modality, offering advantages to the operating surgeon (improved haemostasis, excellent manoeuvrability) and patients (reduced pain and scarring). Complications are largely predictable in nature, but the surgical team should be aware of potential issues to ensure safe, effective patient care.